2021
DOI: 10.1063/5.0064723
|View full text |Cite
|
Sign up to set email alerts
|

Strong negative electrothermal feedback in thermal kinetic inductance detectors

Abstract: We demonstrate strong negative electrothermal feedback accelerating and linearizing the response of a thermal kinetic inductance detector (TKID). TKIDs are a proposed highly multiplexable replacement to transition-edge sensors and measure power through the temperature-dependent resonant frequency of a superconducting microresonator bolometer. At high readout probe power and probe frequency detuned from the TKID resonant frequency, we observe electrothermal feedback loop gain up to L ≈ 16 through measuring the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…It combines the multiplexing advantage of KIDs with the proven performance of bolometric designs in TES detectors, at the expense of fabrication complexity. It has recently been shown that the thermal circuit performs similarly to a TES, with the RF readout power providing a mechanism for electrothermal feedback that is essential to achieving the stability and dynamic range required [59]. Early examples of TKIDs focused on development of sensors for detection of x-rays [61,62]; however, new mm-wave designs for future CMB experiments are underway [63], as shown in Figure 6.…”
Section: Thermal Kinetic Inductance Detectorsmentioning
confidence: 99%
“…It combines the multiplexing advantage of KIDs with the proven performance of bolometric designs in TES detectors, at the expense of fabrication complexity. It has recently been shown that the thermal circuit performs similarly to a TES, with the RF readout power providing a mechanism for electrothermal feedback that is essential to achieving the stability and dynamic range required [59]. Early examples of TKIDs focused on development of sensors for detection of x-rays [61,62]; however, new mm-wave designs for future CMB experiments are underway [63], as shown in Figure 6.…”
Section: Thermal Kinetic Inductance Detectorsmentioning
confidence: 99%
“…Whatever the source, the bottleneck in the recombination of these quasiparticles is their accompanying background distribution of phonons and the phonon escape time into the substrate [83]. This feature lends itself to the simple model where the quasipar ticle temperature is decoupled from the phonon temperature and has been useful in mod eling the response of Thermal Kinetic Inductance Detectors (TKIDs) [73,84,85]. For nonthermal sensors like MKIDs, this model has also been shown to be applicable to the nonequilibrium creation of quasiparticles by a photon signal, which allows us to use it in this dissertation [86].…”
Section: Quasiparticle Densitymentioning
confidence: 99%